Improving Feed Intake, Digestibility, Rumen Fermentation, and Blood Profiles in Kacang Goats through Pueraria phaseoloides Supplementation in Kume Grass Hay Diets - Benu, I.; Jelantik, I. G. N.; Mullik, M. L.; Malelak, G. E. M.; Oematan, G.; Laut, M. M. (Tropical Animal Science Journal, 2024)
This study was conducted to investigate the effects of supplementing Pueraria phaseoloides on feed intake, nutrient digestibility, rumen fermentation, and blood profiles in male Kacang goats fed Kume grass hay as a basal diet. Twelve male Kacang goats aged between 6 and 8 months with a mean body weight of 13.63 ± 1.40 kg were randomly assigned to four dietary treatments (three goats per treatment) in a 3x4 incomplete Latin square design. The treatments consist of a control group (P0) receiving grass hay and concentrate and three groups supplemented with 10% (P10), 20% (P20), and 30% (P30) P. phaseoloides of protein requirement on a dry matter basis. The data obtained in this study were statistically analyzed using the GLM procedure following ANOVA in SPSS Statistics for Windows, version 22. The results indicated that P. phaseoloides significantly (p<0.05) increased feed intake, with goats receiving P. phaseoloides consuming more dry matter compared to the control group (P0). Furthermore, nutrient digestibility improved (p<0.05) with P. phaseoloides supplementation. However, rumen fermentation characteristics, including NH3-N concentration, VFA concentration, and ruminal pH, did not differ significantly among the dietary treatments. Additionally, there were no significant differences in blood profiles among the Kacang goats under different dietary treatments. In conclusion, supplementation of P. phaseoloides in male Kacang goats fed Kume grass hay as a basal diet improved feed intake and nutrient digestibility but had no significant effect on rumen fermentation or blood profiles. Therefore, P. phaseoloides can be used as a feed supplement for ruminants consuming low-quality grass.